Analisis Resepsi Khalayak Terhadap Pesan Maskulinitas Dalam Iklan Semua Juga Bisa Pada Instagram Ms Glow For Men (The Commercium, 2023)
This study uses reception analysis that focuses on the recipient's audience in viewing the MS Glow For Men 'All also Can' advertisement which contains the concept of #BreaktheBeautyStandard. This concept is new in the field of men's skincare advertising because it relates to one's appearance and self-confidence. This study also uses reception theory with a qualitative approach whose results are divided into 3 categories, namely the Hegemonic Dominant Position, the Negotiated Position and the Opposition Position. Data collection was carried out through in-depth interviews with ten informants where there were several categories that became a common thread to determine informants, including men with an age range of 17-40 years, having bad or good experiences about their physical appearance, especially their face and self-confidence, often doing outdoor activities. room and watch the 'Everyone Can' ad on Instagram MS Glow For Men.